A multi-reader in vitro study using porcine kidneys to determine the impact of integrated circuit detectors and iterative reconstruction on the detection accuracy, size measurement, and radiation dose for small (<4 mm) renal stones. (August 2017) - Wells, Michael L; Froemming, Adam T; Kawashima, Akira; Vrtiska, Terri J; Kim, Bohyun; Hartman, Robert P; Holmes, David R; Carter, Rickey E; Bartley, Adam C; Leng, Shuai; McCollough, Cynthia H; Fletcher, Joel G
Background: Detection of small renal calculi has benefitted from recent advances in computed tomography (CT) scanner design. Information regarding observer performance when using state-of-the-art CT scanners for this application is needed. Purpose: To assess observer performance and the impact of radiation dose for detection and size measurement of <4 mm renal stones using CT with integrated circuit detectors and iterative reconstruction. Material and Methods: Twenty-nine <4 mm calcium oxalate stones were randomly placed in 20 porcine kidneys in an anthropomorphic phantom. Four radiologists used a workstation to record each calculus detection and size. JAFROC Figure of Merit (FOM), sensitivity, false positive detections, and calculus size were calculated. Results: Mean calculus size was 2.2 ± 0.7 mm. The CTDIvol values corresponding to the automatic exposure control settings of 160, 80, 40, 25, and 10 Quality Reference mAs (QRM) were 15.2, 7.9, 4.2, 2.7, and 1.3 mGy, respectively. JAFROC FOM was ≥ 0.97 at ≥ 80 QRM,  ≥ 0.89 at ≥ 25 QRM, and was inferior to routine dose (160 QRM) at 10 QRM (0.72, P  < 0.05). Per-calculus sensitivity remained ≥ 85% for every reader at ≥ 25 QRM. Mean total false positive detections per reader were ≤ 3 at ≥ 80 QRM, but increased substantially for two readers ( ≥ 12) at ≤ 40 QRM. Measured calculus size significantly decreased at ≤ 25 QRM ( P  ≤ 0.01). Conclusion: Using low dose renal CT with iterative reconstruction and ≥ 25 QRM results in high sensitivity, but false positive detections increase for some readers at very low dose levels (≤ 40 QRM). At very low doses with iterative reconstruction, measured calculus size will artifactually decrease.